PELAKSANAAN PENGANUGERAHAN TANDA KEHORMATAN SATYALANCANA KARYA SATYA BAGI PEGAWAI NEGERI SIPIL DI LINGKUNGAN PEMERINTAH DAERAH ISTIMEWA YOGYAKARTA - , ISMOYO RADITYO AJI, Triyanto Suharsono, S.H. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Satyalancana Karya Satya is one of the signs the Honor conferred on any civil servant who has had the job 10 years, 20 years and 30 years continuously and shows loyalty, competence, honesty and kedisiplinanya so that it can be an example for other employees. The implementation of the granting of Honorary mark of Satyalancana Karya Satya are still experiencing various obstacles. Formulation of the problem are taken in the writing of this law i.e. How is the implementation of the granting of Honorary Sign Satyalancana Karya Satya for civil servants in the Government of Yogyakarta special region and The constraints that being a hindrance in the execution of the award a mark of honor Satyalancana Karya Satya for civil servants in the neighborhood of the government yogyakarta special region. These laws empirical research is normative. Data obtained from the results of the research will be analyzed using qualitative methods, which outlines data quality in a regular sentence, runtun, logical, not overlap and effectively so as to facilitate the understanding and interpretation of the data.